Pengaruh Black Carbon Dan Sulfur Terhadap Koefisien Grip Bahan Ban Luar Dengan Batikan Lengkung Pada Lintasan Beton Saat Kondisi Kering Dan Basah - Wargono, Damar, Ir. Pramuko Ilmu Purbo Putro, MT, Muh Alfatih Hendrawan.,ST.,MT (2016)
Tires are important from the vehicle. Tire work system utilizing frictional forces between the surface with the road surface is often called a grip. Many factors affect the grip, one of which the quality of the compound of the tire itself. This study aims to determine how much influence black carbon and sulfur to the coefficient of tire grip on pattern concrete arch in the track dry and wet, the value of tensile strength and hardness of the tire compound. The materials used to make the compound is RSS and synthetic rubber mixed with chemicals carbon black, white oil, ZnO, stearic acid, paraffin wax, MBTS, coumarone resin and sulfur. These materials are mixed using two rollmixing up blended and sheet forming compound. To determine the length of the ripening process is done reomether rubber. The next process of vulcanization of rubber using the mold in the press with a temperature of 1300C. tensile test using a rubber testing equipment with standard ISO. Hardness testing using a tool with a Shore A hardness scale teste with ISO standards. Tests conducted by the grip coefficient of 16.2 KG load for 30 minutes. Based on the results of tests performed, the addition of black carbon and sulfur influence on the coefficient of grip, compound tensile strength values, the value of wear and wear rate of the tire compound. For the coefficient of grip on compound 1 with black carbon and sulfur composition of 50/3 phr had the highest grip coefficient of 0.716, while the compound 3 with a composition of black carbon and sulfur phr 60/4 has the lowest coefficient is 0.696 grip on the concrete track dry conditions and loading of 16.2 kg.